The effects on animal welfare, production and economy when using feed blocks for sheep - Ekholm, Ebba (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
Feed blocks are a feed product where certain ingredients are mixed together, to createa solid block. The goal is to provide the animals with a small supply of nutrients at atime, such as energy, protein and minerals. In large sheep countries like the UK, thefeed blocks fill a function under certain conditions. According to manufacturers offeed blocks there is a growing interest among Swedish sheep farmers today to learn more about these feed blocks. The goal of this study was to contribute with useful information about feed blocks and their positive and negative effect on sheep.